TP53-PTEN-NF1 depletion in human brain organoids produces a glioma phenotype in vitro - Singh, Sanjay K.; Wang, Yan; Habib, Ahmed; Priyadarshini, Mamindla; Kodavali, Chowdari V.; Chen, Apeng; Ma, Wencai; Wang, Jing; Hameed, N. U. Farrukh; Hu, Baoli; Fuller, Gregory N.; Kulich, Scott M.; et al. (Frontiers in Oncology, 2023)
Glioblastoma (GBM) is fatal and the study of therapeutic resistance, disease progression, and drug discovery in GBM or glioma stem cells is often hindered by limited resources. This limitation slows down progress in both drug discovery and patient survival. Here we present a genetically engineered human cerebral organoid model with a cancer-like phenotype that could provide a basis for GBM-like models. Specifically, we engineered a doxycycline-inducible vector encoding shRNAs enabling depletion of the TP53, PTEN, and NF1 tumor suppressors in human cerebral organoids. Designated as inducible short hairpin-TP53-PTEN-NF1 (ish-TPN), doxycycline treatment resulted in human cancer-like cerebral organoids that effaced the entire organoid cytoarchitecture, while uninduced ish-TPN cerebral organoids recapitulated the normal cytoarchitecture of the brain. Transcriptomic analysis revealed a proneural GBM subtype. This proof-of-concept study offers a valuable resource for directly investigating the emergence and progression of gliomas within the context of specific genetic alterations in normal cerebral organoids.